2022
DOI: 10.1128/aem.00357-22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clonal Diversity of over 1,200 Listeria monocytogenes Isolates Collected from Public Access Waters near Produce Production Areas on the Central California Coast during 2011 to 2016

Abstract: Listeria monocytogenes serotype 4b and 1/2a strains are implicated in most listeriosis, and hypervirulent listeriosis stems from strains containing pathogenicity islands LIPI-3 and LIPI-4. The waters and sediments in the Central California Coast agricultural region contain widespread and diverse L. monocytogenes populations, and all the isolates contain intact virulence genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 113 publications
8
19
0
Order By: Relevance
“…Notably, none of the 218 isolates from natural environments contained biocide resistance genes qacH , bcrABC , or inlA PMSC mutations. This concurs with a recent study of L. monocytogenes collected from surface waters in California ( 83 ), in which qacH and bcrABC were detected in 0 and 18 isolates, respectively, while inlA PMSC mutations were present in only four of 1,248 examined isolates. In contrast, we identified qacH or bcrABC genes in 45% and inlA PMSC mutations in 51% of isolates from food processing environments.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, none of the 218 isolates from natural environments contained biocide resistance genes qacH , bcrABC , or inlA PMSC mutations. This concurs with a recent study of L. monocytogenes collected from surface waters in California ( 83 ), in which qacH and bcrABC were detected in 0 and 18 isolates, respectively, while inlA PMSC mutations were present in only four of 1,248 examined isolates. In contrast, we identified qacH or bcrABC genes in 45% and inlA PMSC mutations in 51% of isolates from food processing environments.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, none of the 218 isolates from natural environments contained biocide resistance genes qacH , bcrABC , or inlA PMSC mutations. This concurs with a recent study of L. monocytogenes collected from surface waters in California (83), in which qacH and bcrABC were detected in zero and 18 isolates respectively, while inlA PMSC mutations were present in only four of 1248 examined isolates. In contrast, we identified qacH or bcrABC genes in 45% and inlA PMSC mutations in 51% of isolates from food processing environments.…”
Section: Discussionsupporting
confidence: 93%
“…Although not presenting a Premature Stop Codon Mutation in the inlA gene nor the SSI-1, both associated with an increased production of biofilm, as reported in previous studies ( Keeney et al, 2018 ; Upham et al, 2019 ; Mahoney et al, 2022 ), all the strains carried several genetic markers for biofilm production. In particular luxS , for a S-ribosylhomocysteinase, recO encoding the DNA repair protein RecO and lmo2504 for a cell wall-binding protein were found in all the genomes ( Pasquali et al, 2018 ; Gorski et al, 2022 ). The lmo0673 gene, encoding an hypothetical protein and reported as marker of biofilm production by Pasquali et al (2018) , was also found.…”
Section: Discussionmentioning
confidence: 99%